Case-based interprofessional learning for undergraduate healthcare professionals in the clinical setting. Issue 1 (2nd January 2017) - Nasir, Jamal; Goldie, Julie; Little, Annabel; Banerjee, Debasish; Reeves, Scott
ABSTRACT: Interprofessional learning (IPL) within the healthcare setting has well documented positive outcomes for patients, yet it is not widely offered at the undergraduate level, particularly in a clinical setting. We set up case-based teaching scenarios involving a real patient, aimed at small groups of four students representing two or more healthcare professions. The aim of the sessions was to give students a greater awareness of the roles of all the different healthcare professions involved in patient care in a hospital setting. Weekly sessions were offered on six wards covering different clinical specialties. Three hundred and twenty-nine undergraduate students from different healthcare professions (nursing, medicine, pharmacy, midwifery, physician associate, physiotherapy, occupational therapy, speech, and language therapy) each attended one IPL session during the current academic year. Students were given an evaluation sheet at the end of each session to be filled out anonymously. Forty per cent of the students reported experiencing interprofessional case-based learning for the first time. Over 90% of students agreed or strongly agreed with a list of statements promoting the advantages and benefits of case-based IPL for undergraduate students and many of them requested more sessions. Seventy per cent of all respondents stated they would alter their future professional behaviour as a result of this session. We propose to introduce the sessions into the undergraduate curriculum across all healthcare related professions.